2016
DOI: 10.1007/s10334-016-0547-2
|View full text |Cite
|
Sign up to set email alerts
|

Automated assessment of thigh composition using machine learning for Dixon magnetic resonance images

Abstract: Our proposed method based on machine learning produces accurate tissue quantification and showed an effective use of large information provided by the four contrast images from Dixon MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
4
29
0
Order By: Relevance
“…This difference between two readers is consistent with results from previous studies that reported an interobserver variability between manual segmentations of two different readers of 18.4/ 14.7% for the IMF, before/after quality control, respectively [45]. Yet, the DSC observed for IMF using data from the same reader compares quite favorable to the literature, while the DSC achieved with data from the 2nd reader is still comparable with the best achieved results of 0.80 in a study of Yang et al using DIXON MRIs [22]. Further, since the observed effect was systematic and therefore similar for all patients, measuring (side) differences or longitudinal change in the IMF may not be strongly affected.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This difference between two readers is consistent with results from previous studies that reported an interobserver variability between manual segmentations of two different readers of 18.4/ 14.7% for the IMF, before/after quality control, respectively [45]. Yet, the DSC observed for IMF using data from the same reader compares quite favorable to the literature, while the DSC achieved with data from the 2nd reader is still comparable with the best achieved results of 0.80 in a study of Yang et al using DIXON MRIs [22]. Further, since the observed effect was systematic and therefore similar for all patients, measuring (side) differences or longitudinal change in the IMF may not be strongly affected.…”
Section: Discussionsupporting
confidence: 63%
“…There exist several semi-automated [16][17][18][19][20][21] and fully automated [22][23][24][25] tools for thigh tissue volume and CSA segmentation to overcome the challenges in capturing the complex morphology and texture of thigh muscle and adipose tissue that are complicated by considerable intersubject variability ( Fig. 1) and potentially also artefacts as intensity distortions.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is interesting that in elderly subjects, muscle mass declines at a slower rate than strength, emphasizing a strong role of muscle fat infiltration and potentially of the amount of perimuscular fat. A number of diagnostic techniques mostly based on magnetic resonance imaging (MRI) have been introduced [11][12][13][14] for the assessment of fat. In the present study, multi-point T 2 *-corrected Dixon MRI and multi-echo T 2 -corrected magnetic resonance spectroscopy (MRS) were used to measure proton density fat fraction (PDFF) and proton density water fraction (PDWF) while minimizing MR-specific effects.…”
Section: Introductionmentioning
confidence: 99%
“…Andrews et al employed a probabilistic shape representation for the segmentation of the thigh muscle heads and reported a mean DSC of 0.81 ± 0.07 [ 28 ]. Using a voxel classifier-based technology combined with morphological operations for the segmentation of thigh muscles and adipose tissue, Yang et al [ 26 ] reported DSCs of 0.96 ± 0.03 for the SCF, 0.80 ± 0.03 for the IMF and 0.97 ± 0.01 for the combined thigh muscles (quadriceps, hamstrings, adductors and sartorius) when the algorithm was applied to four contrast Dixon MR images and somewhat lower DSCs when the algorithm was applied to fat and water suppressed (SCF 0.94 ± 0.04, IMF 0.68 ± 0.10 and combined thigh muscle 0.96 ± 0.03) or unsuppressed (SCF 0.80 ± 0.10, IMF 0.37 ± 0.13 and combined thigh muscle 0.73 ± 0.21) MR images only. Karlsson et al used a multi-atlas segmentation approach to automatically segment the lean muscle tissue from whole body intensity corrected water-fat separated MRIs and reported a true positive volume fraction of 0.93 ± 0.01 to 0.93 ± 0.03 for the automated thigh segmentation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%